Inskrypcje nagrobne jako element przestrzeni sepulkralnej (na przykładzie nekropolii zelowskiej) - Balowska, Grażyna (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
The subject of the analysis are tombstone inscriptions as a basic element of the sepulchral space of the cemetery of the Evangelical-Reformed parish in Zelów which brings together descendants of the Czech religious immigrants. The author assumes that the tombstone inscription is a lingual-iconic message of a specific, conventionalized structure which includes mandatory and optional verbal components (personal data, initial formulae, additional information about the deceased, final formulae) and the iconic elements (symbols, images of the deceased). Necropolis in Zelów as a denominational cemetery is characterized by a modesty in decor, which is reflected in tombstone inscriptions: especially the relatively narrow symbolism or final formulae resources coming mostly from the Holy Bible.
Keywords: sepulchral space; denominational cemetery; tombstone inscriptions; onomastic inscriptions; initial formulae; final formulae; iconic elements